PRINSIP-PRINSIP PEMBANGUNAN JALAN BERKELANJUTAN - Greece Maria Lawalata (Jurnal Transportasi, 2013)
Road is one of the transport infrastructure that plays a role in the life of the Indonesian nation and promote the general welfare. The use of materials and non-renewable natural resources can be a problem for future generations. Giving priority to only one road users on road design phase, before and after the implementation of the road construction, will be a problem for other road users. Development program that takes into account social, economic, and environment has been proclaimed by many countries and has been a mutual agreement as sustainable development. Efforts that lead to a sustainable development in Indonesia are to consider the principles of sustainable development path that has been used by other countries. This paper identifies criteria for sustainable development and determines criteria that allow for the achievement of sustainable road in Indonesia. The results indicate that the concept into a sustainable development is the fulfillment of the needs of the present generation without compromising the ability of future generations fulfillment, improve the economic, environmental quality, and equality of rights. The criteria for a sustainable road management are efficiency, mobility, safe and comfortable, community participation, restrictions on emissions, natural resources, habitats, and ecosystems.Keywords: sustainable road, sustainable development, sustainable criteria